Association between three genetic variants in kallikrein 3 and prostate cancer risk. Issue 6 (30th November 2018) - Ding, Wei-Hong; Ren, Ke-Wei; Yue, Chuang; Zou, Jian-Gang; Zuo, Li; Zhang, Li-Feng; Bai, Yu; Okada, Atsushi; Yasui, Takahiro; Mi, Yuan-Yuan
Abstract : Background: Epidemiological studies have assessed the association between kallikrein 3 (KLK3) polymorphisms and prostate cancer (PCa) susceptibility. However, published data on this association are somewhat inconclusive. Methods: Articles investigating the association between three KLK3 (rs1058205, rs2735839, and rs266882) variants and PCa susceptibility were searched from online databases, which included 35, 838 patients and 36, 369 control participants. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to demonstrate the strength of the association. We also utilized ELISA to detect serum expression of KLK3. In addition, in silico tools were adopted to evaluate the relationship of KLK3 expression and PCa survival time. Results: The overall results indicated that polymorphism T>C of rs1058205 was associated with decreased risk of PCa (allele contrast: OR = 0.75, 95% CI = 0.64–0.88, P heterogeneity < 0.001; homozygote comparison: OR = 0.58, 95% CI = 0.42–0.81, P heterogeneity < 0.001), particularly in Caucasian population (allele contrast: OR = 0.77, 95% CI = 0.65–0.91, P heterogeneity < 0.001; homozygote comparison: OR = 0.58, 95% CI = 0.41–0.82, P heterogeneity < 0.001). No association was observed between the polymorphism A>G of rs2735839 and risk of PCa. In addition, no association was observed between polymorphism A>G of rs266882 and risk of PCa. Serum KLK3 levels in PCa patients carrying CC/CT genotypes were statistically lower than those carrying TT genotypes. Conclusion: This meta-analysis suggests that rs1058205 polymorphism of KLK3 is a risk factor for PCa development, polymorphism T>C of rs1058205 is associated with decreased susceptibility to PCa particularly in Caucasian population.